Artisanal negative pressure therapy as an adjuvant to autograft skin in orthopedic trauma - Reginaldo Passoni; Jéssica Rosin; Daniela Patrícia Tres; Roger Rodrigues Peres; Danielli Piatti Carvalho; Lili Marlene Hofstatter (Universidade Federal de Santa Maria, 2015)
Aim: to describe the experience with the execution of artisanal negative pressure therapy as an adjunct to skin autograft in orthopedic trauma. Method: report based on practical experience on clinical management of complex wound in patients with an orthopedic trauma. There were initial assessment, enzymatic debridement, surgical dressings and debridement with negative pressure therapy. Results: the use of subatmospheric therapy of artisanal way showed significant positive outcomes, similar to those obtained with the use of commercialized products. It enabled the repair of complex tissue injury and helped autograft successfully. Final Remarks: the artisanal negative pressure therapy shows good effectiveness and efficiency, making it an option for health institutions to small and medium businesses whose financial resources do not support the acquisition of specific business models for this purpose